Determinants of participation and detection rate of upper gastrointestinal cancer from population‐based screening program in China. (27th September 2019) - Guo, Lanwei; Zhang, Shaokai; Liu, Shuzheng; Zheng, Liyang; Chen, Qiong; Cao, Xiaoqin; Sun, Xibin; Qiao, Youlin; Zhang, Jiangong
Abstract: Upper gastrointestinal cancer (UGC) screening has been widely implemented in many Asian countries. However, there is little evidence of participation and diagnostic yields in population‐based UGC screening in China. The participation rate and detection of upper gastrointestinal lesions in this program were reported and related factors were explored. The analysis was conducted in the context of the Cancer Screening Program in Urban China, which recruited 179 002 eligible participants aged 40‐74 years from three cities in Henan province from 2013 to 2017. A total of 43 423 participants were evaluated to be high risk for esophageal cancer or gastric cancer by an established risk score system and were subsequently recommended for endoscopy. Of 43 423 with high risk for UGC, 7996 subjects undertook endoscopy (participation rate of 18.4%). We found that male sex, high level of education, marriage, smoking, current alcohol drinking, lack of physical activity, history of upper gastrointestinal system disease, and family history of UGC were associated with increased participation of endoscopy screening. Overall, 15 UGC (0.19%), 275 squamous epithelial dysplasia (3.44%), and 33 intraepithelial neoplasm (0.41%) cases were detected. Several factors including age, sex, smoking, current alcohol drinking, lack of physical activity, and dietary intake of processed meat were identified to be associated with the presence of upper gastrointestinal lesions. Health promotion campaigns targeting the specific group of individuals identified in our study will be helpful for improvement of the adherence of UGC screening in population‐based cancer screening programs. Participant rate and yield of UGC screening will provide important references for evaluating the effectiveness and cost‐effectiveness of cancer screening in China. Abstract : Endoscopy is effective in terms of detecting esophageal cancer, gastric cancer, and precursors. The adherence to screening endoscopy in this high‐risk population is relatively low and factors associated with the willingness to accept endoscopy screening were identified. Risk factors associated with upper gastrointestinal lesion in Chinese population were identified.